2021
DOI: 10.3389/fcell.2021.640399
|View full text |Cite
|
Sign up to set email alerts
|

Excess Glucose Impedes the Proliferation of Skeletal Muscle Satellite Cells Under Adherent Culture Conditions

Abstract: Glucose is a major energy source consumed by proliferating mammalian cells. Therefore, in general, proliferating cells have the preference of high glucose contents in extracellular environment. Here, we showed that high glucose concentrations impede the proliferation of satellite cells, which are muscle-specific stem cells, under adherent culture conditions. We found that the proliferation activity of satellite cells was higher in glucose-free DMEM growth medium (low-glucose medium with a glucose concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 39 publications
5
21
0
Order By: Relevance
“…However, data suggest that high glucose concentrations may induce SC lipogenesis [ 19 , 20 ]. Recently, data suggest that excess glucose can even impede SC proliferation when comparing a serum-free DMEM and HGDMEM culture media [ 21 ]. While our data are not consistent with Furuichi and colleagues, as they do not reveal decreased proliferation in higher glucose containing basal media, they may indicate that the use of LGDMEM is more optimal than the HGDMEM media as both DMEM media supported MRF+ cells in proliferation and fusion of SC in differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, data suggest that high glucose concentrations may induce SC lipogenesis [ 19 , 20 ]. Recently, data suggest that excess glucose can even impede SC proliferation when comparing a serum-free DMEM and HGDMEM culture media [ 21 ]. While our data are not consistent with Furuichi and colleagues, as they do not reveal decreased proliferation in higher glucose containing basal media, they may indicate that the use of LGDMEM is more optimal than the HGDMEM media as both DMEM media supported MRF+ cells in proliferation and fusion of SC in differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In a cell model using mouse myoblasts C2C12, high glucose exposure of 25 mM was shown to accelerate myogenesis by rearranging SUMO enzyme transcripts and SUMO proteins [55]. However, other experiments with C2C12 have shown that even higher glucose concentrations of 60 mM inhibit the expression of the MyoD and myogenin genes, as well as the Akt signal, suppressing skeletal muscle differentiation [56]. High glucose was also shown to interfere with the proliferation of muscle-specific stem cells and satellite cells under adherent culture conditions [57].…”
Section: Intrauterine Hyperglycaemia-mimicking Cell Modelmentioning
confidence: 95%
“…Satellite cells were cultured according to our previous report 49 but with some modifications. Briefly, each type of muscle fibre was pooled and incubated with Accutase (Innovative Cell Technologies, SAN, USA) for 10 min at room temperature and cultured on Matrigel-coated dishes.…”
Section: Methodsmentioning
confidence: 99%